STUDI ANALISIS PENELITIAN KEBIJAKAN PENDIDIKAN - Rosyidi; Muhammad Syaifudin (Al-mujahidah, 2024)
Education today has become an integral part of the public sphere. For example, how the government created and implemented the National Examination (UN) policy and then turned it into a Computer-Based National Assessment (ANBK) activity, an evaluation program organized by the Ministry of Education and Culture. This evaluation program is intended to improve the quality of education by photographing the input, process and output of learning in all educational units. This policy has advantages and disadvantages. This means that the national exam is not only a concern for certain people or groups, but also a concern for Indonesian society as a whole, therefore a new policy has emerged, namely the Computer-Based National Assessment (ANBK). The aim of writing this journal is to examine educational policy research so that it can be used as a consideration in making educational policies in the future. Meanwhile, the writing method in this journal uses the library method, where the study sources come from literature that discusses education policy research